Absorbance Ratio Optimization as a Function of TiO2-POE Nanolubricant Spectrophotometric Wavelength Using the Quadratic Design on One Factor at a Time - Nugroho, Agus; Rizalman, Mamat; Bo, Zhang; Wan Hamzah, Azmi; Mohd Fairusham, Ghazali; Yusaf, Talal; Khoerunnisa, Fitri (Springer, Singapore, 2023)
Errors in the UV visible spectrophotometry analysis’ selection of spectral peaks can lead to errors in the nanolubricant stability analysis. Despite the fact that the spectral peak results are compared at the same peak, it is critical to identify the correct spectral to avoid errors in the nanolubricant stability analysis results. In this study, one factor at a time (OFAT) based on surface response was adopted to determine the effect of wavelength selection on the absorbance ratio of TiO2-POE nanolubricant. The TiO2-POE sample was prepared using a two-steps approach. The sample was ultrasonicated for 100 min using a homogenizer. UV visible spectrophotometry analysis was performed on day 1 and 15 to determine the absorbance ratio. Sixteen runs were performed using a quadratic design to acquire experimental data were fitted. The ANOVA analysis discovered that the experimental statistics were well suited to the polynomial model, with an R2 value of 0.9970 and a model F-value of 2154.24. The findings suggest that the optimum wavelength is 500 nm with an absorbance value of 0.901239 and a desirability level of 1.0.